1990
DOI: 10.1002/acp.2350040506
|View full text |Cite
|
Sign up to set email alerts
|

Judgmental asymmetry in the exercise of police discretion

Abstract: Police officers and probationer constables rated 40 sets of circumstances as to how far each would influence them to prosecute or not prosecute a motorist stopped for speeding. The distribution of responses about the ipsative means exhibited an asymmetry, consistent with the maximum salience bias towards a negative proportion of lle (Tuohy and Stradling, 1987). This asymmetry occurred in both directions, differentiating between a minority group for whom 'prosecute' was the negative pole and a majority for whom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1992
1992
2008
2008

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Two groups of subjects were studied. The police group consisted of 165 Scottish police officers (154 M and 11 F), with a mean age of 34.1 years (SD=7.1); the low number of female respondents in this group reflects the relatively small proportion of women in the police service (Stradling et al, 1990;Walklate, 1992). The rank structure of the sample was as follows: 114 constables, 11 detective constables, 22 sergeants, seven detective sergeants, five inspectors, two detective inspectors, and one superintendent (three respondents did not disclose their rank).…”
Section: Subjectsmentioning
confidence: 99%
“…Two groups of subjects were studied. The police group consisted of 165 Scottish police officers (154 M and 11 F), with a mean age of 34.1 years (SD=7.1); the low number of female respondents in this group reflects the relatively small proportion of women in the police service (Stradling et al, 1990;Walklate, 1992). The rank structure of the sample was as follows: 114 constables, 11 detective constables, 22 sergeants, seven detective sergeants, five inspectors, two detective inspectors, and one superintendent (three respondents did not disclose their rank).…”
Section: Subjectsmentioning
confidence: 99%
“…Tuohy also saw "maximal differentiation of negative evaluation as a basic operating characteristic of the affective mediator" (p. 49). For example, Stradling et al (1990) reported that when 522 police officers and probation constables rated 40 sets of circumstances as to how far each would influence them to prosecute or not prosecute a motorist stopped for speeding, "the distribution of responses about the ipsative means exhibited an asymmetry, consistent with the maximum salience bias towards a negative proportion of lle" (p. 409), that is, approximately 37%. Tuohfs hypothesis seems consistent with Lefebvre's (1990,199213) proposal that an automatic mechanism for "fast reflexion" determines that the overall proportion of negative judgments will be, on average, close to 0.37.…”
Section: )mentioning
confidence: 83%
“…Presumably the ratings reported by Toglia et al reflect operations carried out at the schematic or conceptual levels defined by Leventhal and Scherer; it can be suggested, however, that the effects of an early informational tendency may continue to reverberate through higher levels and later stages of this hypothetical SEC process. Such an on-going reverberation, although normally over-written by later processing characteristics, would give the informational mechanism the status of a 'weak background force' (Stradling, Tuohy and Harper, 1990), and would account for the covert nature of its effects in normative data.…”
Section: Discussionmentioning
confidence: 99%